TERUG NA DIE TOEKOMS: OOR DIE SAMEHANG TUSSEN RITUELE TYD EN IDENTITEIT - Wepener, Cas (Scriptura, 2004)
Back to the Future: On the Connection between Ritual Time and Identity This paper is an attempt to illustrate how ritual time figures in the formation of identity, and specifically how ritual time can play a positive, constructive role in the establishment of Christian identity. First, the notion of time is discussed from both a phenomenological and a liturgical perspective. Phenomenologically, time is a construction that draws on nature and historical memory to order reality, but theologically that order is broken into and broken open by the incarnation, death and resurrection of Christ to reveal to us God’s future. After this identity is discussed as a cumulative social construction that takes place in space and over time. Identity is constructed by means of symbols with which people identify or with which they are identified. Time itself can also become such a symbol that constructs identity. As such, the liturgical enactment of ritual time - the memory of God’s future that breaks into our reality - can contribute to the formation of Christian identity. Therefore it is important to continually review and actively make use of time as a symbol in the ritual formation of Christian identity.